Podcast-Based Learning Innovation in Islamic Education Management: Enhancing Santri’s Understanding of Fiqh Muʿāmalāt in the Digital Transformation Era - Abdul Haris; Jazilurrahman (Journal of Educational Management Research, 2026)
This study aims to provide an in-depth understanding of Santri Fiqh Podcast as a learning innovation within Islamic Education management to enhance santri’s understanding of Fiqh Muʿāmalāt in the era of digital transformation. Employing a qualitative approach with a case study design, the research was conducted at Syahamah Islamic Boarding School, Probolinggo, from October to December 2025. Data were collected through participant observation, in-depth interviews, and documentation. Data analysis followed the Miles and Huberman interactive model, including data collection, reduction, display, and conclusion drawing. The findings reveal that the implementation of the Santri Fiqh Podcast contributes to improved understanding of Fiqh Muʿāmalāt through two main strategies: (1) the integration of digital technology into Islamic learning management and (2) the internalization of Fiqh Muʿāmalāt values through systematically managed podcast content. From an educational management perspective, the podcast functions as a strategic learning resource that supports planning, implementation, and evaluation of digital-based PAI instruction. The study implies that podcast-based learning enhances student engagement, learning effectiveness, Islamic literacy, learning outcomes, and santri motivation, while strengthening digital innovation management in Islamic boarding schools.